INFLUENCE OF COMPENSATION AND MOTIVATION ON TEACHER PERFORMANCE IN ISLAMIC JUNIOR HIGH SCHOOLS (MADRASAH TSANAWIYAH) - Nenden Quratul Aini; Wia Adawiyah Muthoharoh (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study empirically analyzes the partial and simultaneous influence of compensation and motivation on teacher performance in two private Islamic Junior High Schools (Madrasah Tsanawiyah) in Bandung Regency. A quantitative method employing a census survey approach was applied to the entire population of teachers (N=51). Data analysis utilized Multiple Linear Regression to test the established hypotheses. The results indicate that both compensation and motivation have a positive and statistically significant influence on teacher performance, both partially and simultaneously. A critical finding reveals that the impact of compensation is primarily driven by non-financial dimensions, specifically a supportive work environment and positive collegial relations, which act as essential Hygiene Factors for teacher satisfaction. The two variables jointly contribute significantly to teacher performance (F = 47.161; Sig. 0.000), with a strong predictive capability R2 of 66.3%. The study concludes that teacher performance in Islamic schools is a synergistic function of institutional support. Therefore, performance improvement strategies must prioritize strengthening a supportive work climate (non-financial compensation) as the principal driver of sustained achievement motivation, rather than relying solely on financial incentives.